Evaluation of Latent Fingerprints for Drug Screening in a Social Care Setting. Issue 1 (2nd December 2020) - Pollard, Caroline; Sievers, Claudia; Royall, Paul G; Wolff, Kim
Abstract: Sweat deposited via latent fingerprints (LFPs) was previously used to detect cocaine, opioids, cannabis and amphetamine via a point-of-care test (POCT). This screening method combined non-invasive sampling with a rapid result turnaround to produce a qualitative result outside of the laboratory. We report the novel application of a LFP drug screening test in a social care setting. Clients were tested on either an ad hoc or a routine basis using the POCT DOA114 (Intelligent Fingerprinting Ltd) drug screening cartridge. Screening cutoff values were 45, 35 and 95 pg/fingerprint for benzoylecgonine (BZE), morphine and amphetamine analytes, respectively. Confirmation LFP samples (DOA150, Intelligent Fingerprinting Ltd) and oral fluid (OF) were analyzed using ultra-performance liquid chromatography with tandem mass spectrometry. Thirty-six clients aged 36 ± 11 years participated (53% females). Individuals self-reported alcohol consumption (39%) and smoking (60%). Of 131 screening tests collected over 8 weeks, 14% tested positive for cocaine, 2% tested positive for opioids and 1% tested positive for amphetamine. Polydrug use was indicated in 10% of tests. Of 32 LFP confirmation tests, 63% were positive for cocaine and BZE. Opioids were also detected (31%), with the metabolite 6-monoacetylmorphine (6-MAM) being the most common (16%). In OF, cocaine was the dominant analyte (9%) followed by 6-MAM (5%). On comparing positive LFP screening tests with positive OF samples, we found that 39% and 38% were cocaine and opiate positive, respectively. Of the drugs screened for via the LFP POCT, cocaine was the most prevalent analyte in LFP and OF confirmation samples. The study is a step change in the routine drug screening procedures in a social care setting, especially useful for on-site cocaine detection in clients whose drug use was being monitored. Additionally, testing was easily accepted by clients and social care workers.